(untitled) (Global Journal of Management and Business Research, 2023)
Despite laudable programs by the Nigerian government and policymakers the consumer goods sector in Nigeria continues to experience declining financial performance The research examined the effect of the contribution of the employee dimension of corporate social responsibility on the financial performance of listed consumer goods companies in Nigeria Descriptive and causal research designs were found appropriate for the study The secondary source of data collection via panel data was used Data collection method was corporate responsibility to employee checklist and by extraction from annual reports and accounts of listed consumer goods companies in Nigeria The inferential statistics of multiple regressions were employed to attain the research objective The Python 3 8 and E views 10 were the statistical packages used in the study for data analysis Findings showed a positive and significant effect of corporate responsibility on employees on the financial performance The paper recommends that the consumer goods companies should do more on the corporate responsibility on employees relations to improve employees motivation and corporate reputation and image that has the potential to improve financial performance